The current state of research on Pejerrey (Odontesthes bonariensis) physiology and challenges for aquaculture development - Mechaly, Alejandro (2025)
Pejerrey is a native fish of the Pampas with relevance in aquaculture and sport fisheries. This review integrates current knowledgeon the biology, culture, and physiological adaptations of this species, emphasizing its potential for sustainable aquaculture. From abiological perspective, pejerrey exhibits a unique combination of genotypic and temperature-dependentsex determination, makingit a prime model for studying sex determination in vertebrates. From an aquaculture standpoint, many of the potential limitations ofpejerrey farming have been addressed by focused research, such as the low batch fecundity, poor synchronization of maturation, andlimited sperm availability are now almost completely mitigated by advances in photothermal and hormonal manipulation of maturationand broodstock husbandry. Osmoregulatory studies confirmed that pejerrey is a euryhaline species, thriving in brackish water,which enhances survival and stress tolerance across all life stages, resolving early misconceptions of pejerrey as a strictly freshwaterfish. With survival under control, the low growth rate is now the next research challenge, although it is compensated for by the qualityand high market value of the fish. Triploidy induction, interspecific hybridization with the Patagonian pejerrey, and thermal treatmentsfor sex control offer promising avenues for growth improvement through reproductive suppression or monosex culture. Thesequencing of its genome paves the way for genetic improvement via genomic selection and gene editing. Ongoing nutritional studies are key to optimizing diets, enhancing growth rates, and improving reproductive success. Further investigations on these and otherareas should help realize the aquaculture potential of this economically significant species.